Strengthening the International Monetary System-A Stocktaking. (Policy Papers; Policy Paper, 2016)
In light of the changing contours of the global economy, this paper provides an overview of the challenges facing the International Monetary System (IMS). It seeks to forge a common understanding of the challenges facing the IMS and its shortcomings, and to lay the basis for discussing a possible roadmap for further work on reform areas.